2000
DOI: 10.1038/sj.gt.3301277
|View full text |Cite
|
Sign up to set email alerts
|

A lentiviral vector expressing a fusogenic glycoprotein for cancer gene therapy

Abstract: The gibbon ape leukaemia virus envelope fusogenic membrane glycoprotein (GALV FMG) is a highly potent cytotoxic gene with great potential for use in cancer gene therapy. Here, we show that production of a VSV-G pseudotyped lentiviral vector expressing GALV FMG reconciles the requirements of viral production with the cytotoxic effects of GALV in human cells and has high titres on both dividing and quiescent tumour cells. Direct intratumoral injection of these stocks eradicated progressively growing human tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…7 However, when we cloned the cDNA of the GALV FMG 2,4 downstream of the TDE-SV40 element with the aim of generating melanoma-specific cell killing in vitro, although there was a clear lag period in the formation of syncytia compared with CMV-GALV, significant amounts of cell fusion subsequently developed after 72-96 h (data not shown). Since GALV has such a potent bystander killing effect 2,3 it was clear that it would be necessary to improve the specificity of the transcriptional elements that are used to direct its expression. Therefore, we investigated whether it would be possible to identify an element within the human tyrosinase promoter 8 that would be transcriptionally silent in non-melanoma cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…7 However, when we cloned the cDNA of the GALV FMG 2,4 downstream of the TDE-SV40 element with the aim of generating melanoma-specific cell killing in vitro, although there was a clear lag period in the formation of syncytia compared with CMV-GALV, significant amounts of cell fusion subsequently developed after 72-96 h (data not shown). Since GALV has such a potent bystander killing effect 2,3 it was clear that it would be necessary to improve the specificity of the transcriptional elements that are used to direct its expression. Therefore, we investigated whether it would be possible to identify an element within the human tyrosinase promoter 8 that would be transcriptionally silent in non-melanoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that tumour cells dying through GALV-mediated cell fusion induce hsp70 expression. 2,3 Hsp70 is transcriptionally activated by binding of the HSF-1 transcription 11 to the HSE, a well-defined transcriptional element upstream of a variety of heat shock genes. 9,10 We initially reasoned that by placing one or more HSE upstream of the weak Tyr-300 element, small levels of GALVmediated cell killing might induce endogenous HSF-1 as part of the stress response which would amplify expression from the HSE-Tyr-300 element.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations